2021
DOI: 10.1155/2021/5577486
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Algorithm to Describe the Connection between the Types and Characteristics of Music Signal

Abstract: Music classification is conducive to online music retrieval, but the current music classification model finds it difficult to accurately identify various types of music, which makes the classification effect of the current music classification model poor. In order to improve the accuracy of music classification, a music classification model based on multifeature fusion and machine learning algorithm is proposed. First, we obtain the music signal, and then extract various features from the classification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Sun suggested that third-party recommendations be used in mobile application scenarios. They use the current location of users as context information and collect preferences of other users at the current location as recommendations [ 14 ]. Kim suggested using new features such as harmonic coefficients in features and proposed a more robust music and speech classification algorithm [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…Sun suggested that third-party recommendations be used in mobile application scenarios. They use the current location of users as context information and collect preferences of other users at the current location as recommendations [ 14 ]. Kim suggested using new features such as harmonic coefficients in features and proposed a more robust music and speech classification algorithm [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…Harmonic progression is the horizontal connection of chords, i.e., the sound formed by connecting chords in a certain order. Harmonies are produced simultaneously in music, but they are in harmony with each other [7] , making the music less monotonous and richer in content and being important for harmonizing the musical structure and for composing the musical form. The general style of music can sometimes be inferred from chords.…”
Section: Harmonymentioning
confidence: 99%
“…Melody is the trajectory of sound movement formed by the arrangement and combination of different high and low notes [7] . Melody is the main thread of music and is a critical factor in determining music genres [8] .…”
Section: Melodymentioning
confidence: 99%